Anti-Cancer Pyrimidines in Diverse Scaffolds: A Review of Patent Literature - Kaur, Ramandeep; Kaur, Prabhkirat; Sharma, Sahil; Singh, Gurpreet; Mehndiratta, Samir; M.S. Bedi, Preet; Nepali, Kunal (Recent Patents on Anti-Cancer Drug Discovery, 2015)
Pyrimidine ring is the building unit of DNA and RNA and thus pyrimidine based chemical architectures exhibit diverse pharmacological activities. Among the reported medicinal attributes of pyrimidines, anticancer activity is the most extensively reported. The anticancer potential of pyrimidines in fused scaffolds has also been evidenced through number of research article and patent literature. The pyrimidines based scaffolds have exerted their cell killing effects through varied mechanisms which indicate their potential to interact with diverse enzymes/ targets/receptors. This review article strictly focuses on the patent literature from 2009 onwards. The structure of the potent compounds, their IC50 values, models/assays used for the anticancer evaluation and the enzymes/ receptors/ targets involved have been presented in this compilation. Significant number of patents i.e. 59 have been published on pyrimidine based anticancer agents from 2009-2014 (from 2009 through the present date) which clearly indicate that this heterocycle is an area of focus at present for researchers all over the globe. Moreover, out of the 59 patents published during this period, 32 have been published from 2012 onwards which further highlights the present interest of the researcher towards pyrimidine based anticancer agents. The promising activity displayed by these pyrimidine based scaffolds clearly places them in forefront as potential future drug candidates. The present compilation can be extremely beneficial for the medicinal chemists working on design and synthesis of anticancer drugs.
Keywords: Anticancer